Wives As Breadwinners In The Family from An Islamic Legal Perspective (Case Study in Lambheu Village, Darul Imarah District) - Rabzani Zammima Asri Purba; Fakhrurrazi M. Yunus; Gamal Achyar (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2026)
In Islam and Indonesian marriage law, the husband is positioned as the primary provider (nafkah), while the wife manages household affairs. However, socio-economic changes and certain circumstances such as the husband’s illness, disability, or insufficient income have led some wives in Lambheu Village, Darul Imarah District, to assume the role of the main breadwinner. This shift generates new dynamics, including emotional and social challenges, as well as questions about its compatibility with Islamic legal norms. This study aims to analyze the phenomenon of wives as primary breadwinners in Lambheu Village and to assess its implications for spousal rights and obligations and for the concept of nafkah from the perspective of Islamic law. The research employs a descriptive qualitative design based on fieldwork, combining document analysis, observation, and in-depth interviews. Primary data were obtained from wives who serve as the economic backbone of their families (case-based informants), while secondary data were drawn from fiqh literature, normative sources, and related studies. Data were analyzed through data reduction, data display, and conclusion drawing. The findings show that, from an Islamic legal perspective, the husband remains the principal party responsible for providing financial support, while the wife may work or contribute to family maintenance as long as she continues to observe household responsibilities and does so on the basis of mutual agreement. The Lambheu case indicates that wives typically work due to emergency conditions such as the husband’s illness or financial hardship, highlighting the need for a fair interpretation of role distribution within the family. When carried out wisely and in accordance with Sharia, a wife’s employment is not a violation but rather an effort to strengthen family resilience and harmony. The article recommends strengthening household agreements through deliberation (musyawarah) on role-sharing, enhancing religious guidance and family counseling, and expanding community/state support (access to healthcare, economic empowerment, and social protection) so that wives’ economic contributions do not negate the husband’s nafkah obligation and the family’s overall welfare (maslahah) is maintained.